THE INFLUENCE OF EDUCATIONAL TECHNOLOGY ON WELL-BEING STATUS: A LITERATURE REVIEW - Abdul Feroz Maluleke (International Journal of Educational Best Practices, 2023)
Undoubtedly, Information Technology (IT) has significantly expanded global educational accessibility. Extensive research underscores the need to examine how educational technology adoption affects the well-being of educators and learners, considering education's potential to enhance well-being and mitigate socio-economic challenges. This study aims to comprehensively review the impact of educational technology on human well-being in diverse educational contexts. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic review encompassed databases such as Web of Science, Science Direct, SAGE, and Taylor and Francis. Thirteen selected articles underwent rigorous analysis. Findings reveal contextual variations in the influence of educational technology on well-being, with both positive and negative effects observed. In numerous contexts, a negative correlation between educational technology use and well-being is evident, exacerbated by insufficient training leading to stress among teachers and learners. Quantitative predominance in existing studies suggests a future shift toward qualitative or mixed-method approaches, offering deeper insights into the intricate relationship between educational technology and well-being across diverse settings. In conclusion, urgent interventions are needed to ensure equitable access to educational technologies and training. Such efforts should extend to least developed countries and small island developing states, fostering well-being enhancement and socio-economic progress through holistic technology integration in education.